Économie linguistique dans le français contemporain : approche lexicologique et orthographique - Szabados, Laura (Verbum – Analecta Neolatina, 2024)
The aim of our work is to regroup and analyse several lexical and orthographic phenomena in contemporary French in a theoretical way, from the perspective of linguistic economy, one of the basic elements of language universals. As Zipf (1949) discovered, there is a natural correlation between a word’s frequent use and its brevity or simplicity, which depends on human nature and by which language can be better adapted to speakers’ needs for speed and simplicity in communication (cf. the principle of least effort). This tendency can be noted in contemporary French as well: in certain types of word formation, such as truncation or some neologisms; or in orthography, like Internet language, for example. However, it is always present simultaneously with other partially linguistic phenomena where economy is obviously not a priority, such as inclusive writing or politically correct language.